Molecular regulation of plasma lipid levels during systemic inflammation and sepsis. Issue 2 (April 2019) - Trinder, Mark; Boyd, John H.; Brunham, Liam R.
Abstract : Purpose of review: Sepsis is a common syndrome of multiorgan system dysfunction caused by a dysregulated inflammatory response to an infection and is associated with high rates of mortality. Plasma lipid and lipoprotein levels and composition change profoundly during sepsis and have emerged as both biomarkers and potential therapeutic targets for this condition. The purpose of this article is to review recent progress in the understanding of the molecular regulation of lipid metabolism during sepsis. Recent findings: Patients who experience greater declines in high-density lipoprotein during sepsis are at much greater risk of succumbing to organ failure and death. Although the causality of these findings remains unclear, all lipoprotein classes can sequester and prevent the excessive inflammation caused by pathogen-associated lipids during severe infections such as sepsis. This primordial innate immune function has been best characterized for high-density lipoproteins. Most importantly, results from human genetics and preclinical animal studies have suggested that several lipid treatment strategies, initially designed for atherosclerosis, may hold promise as therapies for sepsis. Summary: Lipid and lipoprotein metabolism undergoes significant changes during sepsis. An improved understanding of the molecular regulation of these changes may lead to new opportunities for the treatment of sepsis.